Enantiomeric behaviour of albendazole and fenbendazole sulfoxides in domestic animals: Pharmacological implications - Capece, Bettencourt P. S. (2009)
Albendazole and fenbendazole are methylcarbamate benzimidazole anthelmintics extensively used to control gastrointestinal parasites in domestic animals. These parent compounds are metabolised to albendazole sulfoxide and fenbendazole sulfoxide (oxfendazole), respectively. Both sulfoxide derivatives are anthelmintically active and are manufactured for use in animals. They metabolites have an asymmetric centre on their chemical structures and two enantiomeric forms of each sulfoxide have been identified in plasma, tissues of parasite location and within target helminths. Both the flavin-monooxygenase and cytochrome P450 systems are involved in the enantioselective biotransformation of these anthelmintic compounds in ruminant species. A relevant progress on the understanding of the relationship among enantioselective metabolism and systemic availability of each enantiomeric form has been achieved. This article reviews the current knowledge on the pharmacological implications of the enantiomeric behaviour of albendazole sulfoxide and oxfendazole in domestic animals.